2021
DOI: 10.1161/jaha.120.020051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Prepregnancy/Early‐Pregnancy Body Mass Index and Pregnancy Smoking and Alcohol on Congenital Heart Diseases: A Parental Negative Control Study

Abstract: Background Congenital heart diseases (CHDs) are the most common congenital anomaly. The causes of CHDs are largely unknown. Higher prenatal body mass index (BMI), smoking, and alcohol consumption are associated with increased risk of CHDs. Whether these are causal is unclear. Methods and Results Seven European birth cohorts, including 232 390 offspring (2469 CHD cases [1.1%]), were included. We applied negative exposure paternal control analyses to expl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 62 publications
4
18
0
Order By: Relevance
“…However, as noted above our imprecise MR results do not rule out an effect, and future larger MR studies are important. Due to the lack of information on alcohol consumption around the time of their partners pregnancy, previous analyses using a negative control design were inconclusive 10 . Recent meta-analyses found consistent modest increases in risk of offspring CHD in mothers reporting alcohol consumption in pregnancy, however, many of the included studies did not adjust for confounders 9,45 , meaning that it is difficult to determine whether the association is a result of alcohol or other characteristics that are related to alcohol and offspring CHDs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, as noted above our imprecise MR results do not rule out an effect, and future larger MR studies are important. Due to the lack of information on alcohol consumption around the time of their partners pregnancy, previous analyses using a negative control design were inconclusive 10 . Recent meta-analyses found consistent modest increases in risk of offspring CHD in mothers reporting alcohol consumption in pregnancy, however, many of the included studies did not adjust for confounders 9,45 , meaning that it is difficult to determine whether the association is a result of alcohol or other characteristics that are related to alcohol and offspring CHDs.…”
Section: Discussionmentioning
confidence: 99%
“…The causal relevance of the results from meta-analyses is unclear, due to many studies not controlling for key confounders and for the risk of residual confounding. Previously, using parental negative exposure control analyses, we found that positive associations between maternal overweight and obesity with offspring CHDs may be being driven by confounding factors 10 . This work found some evidence of an intrauterine effect of maternal smoking on offspring CHDs.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Considering these two criteria, we used paternal exposures measured around the time of pregnancy as a negative exposure control ( Figure 1A ), and offspring dental trauma as a negative control outcome ( Figure 1B ). Parental negative exposure controls have been used previously to explore the intrauterine effects of maternal exposures and offspring outcomes (Brand et al, 2019; K. Taylor et al, 2021).…”
Section: Introductionmentioning
confidence: 99%